Implications of climate warming for hydrology and water balance of small shallow lakes: A case of Wamala and Kawi, Uganda. Issue 4 (1st October 2016) - Natugonza, Vianny; Ogutu-Ohwayo, Richard; Musinguzi, Laban; Olokotum, Mark; Naigaga, Shamim; Kitabona, Janet
Abstract : Climate variability and change that have been intensifying since the 1970s are accompanied by changes in hydrology and water balance of inland aquatic systems. These changes, however, have not been well documented with regard to small and shallow aquatic systems that are more vulnerable. Changes in temperature, rainfall and wind speed around Lakes Wamala and Kawi (Uganda) were examined to provide insight on how the increasing variability and change in climate affect water balance and lake water levels. Around Lake Wamala, average air temperature has increased by 0.018°C y −1 since 1980. Rainfall increased by 9.01 mm y −1 since 1970 and accounted for 79.5% of the water gain during 2011 and 2013 period. However, the gains were exceeded by losses as a result of evaporation that accounted for >85% of the water loss. Despite the increase in rainfall, the mean lake depth of Lake Wamala decreased by 0.015 m y −1, apparently due to high evaporation rates. Around Lake Kawi, average air temperature has increased by 0.036°C y −1 since 1980. Rainfall, however, has decreased, although it still dominates the water inflows, accounting for 83% of the total water gains. Interviews with local fishermen on Lake Kawi indicated that the lake shoreline has receded by ∼50 m over the last two decades. These results suggested that most of the water in small shallow lakes is gained through direct rainfall, but more is lost through evaporation. Therefore, increase in rainfall around these lakes is no longer sufficient to sustain normal lake water levels and lake surface area as long as temperature and wind speed, which enhance evaporation, continue increasing. This has implications for lake productivity processes and needs to be understood and incorporated in management of fisheries and the catchment areas as climate warming intensifies.